The dynamics of micro and small enterprises (MSE) toward bankability with coronavirus pandemic adjustment - Ruslan Prijadi; Permata Wulandari; Fajar Ayu Pinagara; Putri Mega Desiana (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The objective of this study is to elaborate on the development of micro and small enterprises (MSEs) at the bottom of the economy, where most of them began as unbanked micro-ventures and may continue to be micro-enterprises even after being elevated to higher levels. This study contributes to the field of entrepreneurial finance by identifying the factors that influence the drivers and constraints of MSE upgrading. This paper employed models to show how unbanked MSEs transition to bankable ones, as well as to reveal the dynamics of MSEs' transition to bankability during the COVID-19 pandemic. This study's unit of analysis is MSEs, which initially have little or no access to bank loans. This study employs system dynamics (SD) modeling to investigate and manage the multifaceted response system of MSEs' growth toward bankability in the face of a coronavirus pandemic in Indonesia. This study also simulates a coronavirus pandemic outbreak to fine-tune MSEs' progress toward bankability. The dynamic models in this study reveal a number of variables that are critical in accelerating the bankability status of MSE from un-bankable to bankable, namely entrepreneurial MSE time to bankability, channel business, and MSE NPL. Policymakers can create high leverage policies for MSE bankability progression by changing these values.
Keywords: 650; bankability; coronavirus pandemic adjustment; dynamics; Indonesia; micro and small enterprises (MSE)